External cues benefit walking ability of ambulatory patients with spinal cord injury - Amatachaya S. (2014)
Background/objectives: Sensorimotor dysfunction following spinal cord injury (SCI) reduces ability of the patients to perceive information and control movements. They may need alternative sources of input to optimize their walking ability. This study investigated effects of external cues on walking ability in 33 independent ambulatory participants with SCI. Methods: Participants' walking ability was cross-sectionally assessed under three conditions including self-determined fastest walking speed (uncued condition), and fastest walking speed with the use of external cues (visual cue and visuotemporal cue conditions). Walking ability was measured in terms of walking speed, stride length, cadence, and percent step symmetry. Findings of the three conditions were compared using the one-way analysis of variance with repeated measures. Results: When using external cues particularly the visuotemporal cue, participants showed a significant increase in walking speed, stride length, and cadence as compared with those of the uncued condition (P < 0.005). The increment of walking speed was demonstrated even in participants at a chronic stage of injury (post-injury time ≥12 months), with severe SCI (American Spinal Injury Association Impairment Scale C), or who required a walking device. Conclusion: The results suggested the benefit of external cues, particularly the visuotemporal cues, as a potential rehabilitation tool to improve walking speed of individuals with SCI. © The Academy of Spinal Cord Injury Professionals, Inc. 2013.